Aprendizagem de música no cotidiano das organistas da Congregação Cristã no Brasil em Juazeiro do Norte - Brito, Carlos Renato de Lima (2016)
The Christian Congregation in Brazil is an Evangelical Pentecostal Church, founded in 1910, in São Paulo. Today it is present throughout Brazil and in other countries. There are several reasons why this church has a significant place in teaching and learning music, among which may be mentioned: a division of labor between men and women in the execution of hymns during services, the presence of a set curriculum for training musicians in the Church and the way in which the institution is committed to maintaining a music ministry. This study investigated the music education of the organists of the Christian Congregation in Brazil, using case study as a methodological approach. The interviews with the ten organists who participated in the survey were conducted according to the procedures of collection and analysis of data in comprehensive interviews (KAUFFMANN, 2013). Procedures of documentary research (SA-SILVA; ALMEIDA; GUINDANI, 2009) were also adopted to better understand the Constitution of the Christian Congregation and the teaching materials adopted in their music education. Based on Berger and Luckmann's (1983) ideas of daily life, of primary and secondary socialization, of institutionalization and of social role, this study had the general objective to understand the process of learning music of the organists of the Christian Congregation in Brazil in the city of Juazeiro do Norte, Ceará. The specific objectives were to become acquainted with the music education in the Christian Congregation in Brazil and the relationship it has with the music learning of the organists, as well as reflect on the social role of the organists in the Church and the influence this has on the music learning being studied. As a result of this study, it was noted that the music learning process of the organists can be described as familial, religious and institutional. Most of the organists interviewed start learning music at home; these musical experiences play a big part in their memories: their parents' demands regarding practice of the instrument and the times when the family would gather to play. The experience of learning music in the Church is interlaced with the religion professed by the organists, so that learning music is interpreted in terms of the Christian faith. Admission into the Church's music lessons through a vocational direction, the guidance of the instructors for a life "more dedicated to God" and coping with learning difficulties from the perspective of a "dependence on God" are examples of this learning method influenced by religion. In addition, the music learning of the organists is institutional in the sense of being directed by a "minimum program" stipulated by the Church, and the internalization of a social role that is well-defined by the group. These aspects of the organists' music education are interconnected and form a complex phenomenon, considering the social and subjective dynamics of this context.